(untitled) (Communications in Computational Physics, 2025)
This work is devoted to the numerical approximation of three-temperature multi-material hydrodynamics. Such systems are subject to stiff phenomena which require specific care during the discretization. In particular, the so-called discrete equation method is here applied to the radiation transport, in the optically-thick limit. This strategy is shown to be accurate in the presence of in-cell interfaces while being simpler than standard interface reconstruction techniques. It is then incorporated into a three-temperature multi-material scheme whose implicit temporal discretization is based on convex combinations. Stiff test cases eventually establish the scheme’s robustness.